Ekstrak Granul Nanopartikel Kulit Jeruk Sunkist (Citrus Sinensis (L.) Osbeck) Dan Ekstrak Kulit Jeruk Nipis (Citrus Aurantifolia) Terhadap Gambaran Perlemakan Hati Pada Tikus (Rattus Norvegicus) Model Diabetes) - Mutia, Maya Sari; Nabila, Putri; Hamsi, Ulpah Zahara; Lubis, Yolanda Eliza Putri (Jurnal Maternitas Kebidanan, 2024)
Sunkist oranges (Citrus sinensis (L.) Osbeck have a high content of anthocyanins (95% of which are cyanidin-3-glucoside and cyanidine-3-6"-malonyl-glucoside), flavanone (hesperidin and narirutin), as well as hydroxynamic acid (caffeic acid, cumaric acid, cinnamic acid, and ferulic acid), carotenoids, sugars, minerals, and fiber, considered a good food source of bioactive substances with beneficial effects on health. This study aims to examine the potential for liver improvement in mice with a diabetes model after the administration of nanoparticle granules combining sunkist orange peel and lime peel. The design of this experimental research is Post Test Only Control Group Design. Twenty-five male rats of the wistar strain were used which were divided into 5 groups at random, namely the negative control group (aloxan), the positive control group (aquadest), Treatment 1 (aloxan + nanoparticle granules 50mg/kgBB), Treatment 2 (aloxan + nanoparticle granules 100mg/kgBB) Treatment 3 (aloxan + nanoparticle granules 200mg/kgBB). The liver organ was prepared for observation with 10x ocular magnification and 40x objective lens magnification. Liver improvement had an effect on the decrease of SGPT, SGOT, and Histopathological picture of the liver in diabetic model mice after the administration of nanoparticle granules combined with sunkist orange peel and lime peel at concentrations of 50 mg/KgBB, 100 mg/KgBB and 200 mg/KgBB showed significant differences. The best liver improvement is by administering nanoparticle granules a combination of sunkist orange peel and lime peel at a concentration of 200 mg/KgBB. Keyword: Diabetes Mellitus, Sunkist orange and lime peel extracts, fatty live.